Microsimulation Analysis of COVID-19 and Inflation Effects on Romanian Household Income Dynamics - Eva Militaru; Amalia Cristescu; Maria Denisa Vasilescu; Larisa Stanila (Economies)
In recent years, EU member states have faced two significant crises: the COVID-19 pandemic and high inflation, exacerbated by geopolitical instability. These events have led to a decline in household purchasing power. Our study aims to quantify the impact of these crises on household income dynamics in Romania, using data from the EU Survey on Income and Living Conditions and the EUROMOD tax-benefit microsimulation model. We analyze income changes across demographic segments from 2019 to 2021 (COVID-19 period) and 2021 to 2023 (inflation crisis), focusing on household characteristics such as the presence and number of children, the gender of the household head, and the presence of elderly members. Our findings reveal that while disposable income increased from 2019 to 2021, the poorest 10% experienced the smallest gains. In 2022–2023, inflation eroded these increases, and the lower half of the income distribution struggled with reduced earnings and pensions. Despite this, the Gini coefficient for disposable income decreased from 2019 to 2023, indicating a reduced inequality. Our study highlighted that targeted public policy interventions are essential to support vulnerable households and mitigate the effects of economic shocks.